An open secret : the history of unwanted pregnancy and abortion in modern Bolivia - Kimball, Natalie L. (Rutgers University Press, 2020)
"Many women throughout the world face the challenge of confronting an unexpected or an unwanted pregnancy, yet these experiences are often shrouded in silence. An Open Secret draws on personal interviews and medical records to uncover the history of women's experiences with unwanted pregnancy and abortion in the South American country of Bolivia. This Andean nation is home to a diverse population of Indigenous and mixed-race individuals who practice a range of medical traditions. Centering on the cities of La Paz and El Alto, the book explores how women decided whether to continue or terminate their pregnancies and the medical practices to which women recurred in their search for reproductive health care between the early 1950s and 2010. It demonstrates that, far from constituting private events with little impact on the public sphere, women's intimate experiences with pregnancy contributed to changing policies and services in reproductive health in Bolivia"--